Transport And Magnetic Properties Of (Fe100-xVx)75 P15C10 Amorphous Alloys - Karal, MAS; Kamruzzaman, M; Khan, FA (Journal of Bangladesh Academy of Sciences, 2012)
(Fe100-xVx)75 P15C10 (x = 0, 5, 10 and 15) amorphous alloys in the form of ribbon were prepared by the standard melt spinning technique and studied their transport and magnetic properties. The resistivity follows ‘Mooij correlation’ at low temperature (300 - 93) K. The Hall resistivity and the magnetoresistance (MR) were measured in an applied magnetic field up to 0.6T at room temperature (RT = 300 K). Anomalous Hall effect was observed in the Hall resistivity measurement and MR was found to vary 0 - 8%. The saturation magnetization gradually decreased with the increase of V in the alloys at RT. Key words: Resistivity; Mooij correlation; Hall resistivity; Magnetoresistance; Saturation magnetization DOI: http://dx.doi.org/10.3329/jbas.v35i2.9420 JBAS 2011; 35(2): 161-169